2019
DOI: 10.1590/0004-282x20190132
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patients with migraine and tension-type headache in terms of somatosensory amplification and health anxiety

Abstract: Although it is known that anxiety and depressive disorders frequently accompany migraine and TTH, the role of somatic amplification (SSA) and health anxiety in these diseases is not adequately known. Objective: The aim of this study is to compare SSA and health anxiety in patients with migraine or TTH, and healthy controls and to investigate the relationships between SSA, health anxiety, headache characteristics, anxiety and depressive symptoms. Methods: Fifty-four migraine, 50 TTH patients from the outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…Nonetheless, both BDI scores (vs. TTH) and BAI scores (vs. TTH and no headache) were notably higher in patients with migraine, supporting that migraine is often accompanied by psychiatric disorders, of which anxiety and depression are the most widely known and extensively studied. 17,[54][55][56] Indeed, given the longer headache days, higher NRS scores, and headache severity during daily activities as well as higher rate of ER admissions in patients with migraine versus in patients with TTH, our findings are also consistent with previous studies, which reported a relationship of BAI and BDI scores with frequency of episodes and NRS scores in patients with cisgender migraine. 17,57,58 In migraine, the role of testosterone has not been well studied.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Nonetheless, both BDI scores (vs. TTH) and BAI scores (vs. TTH and no headache) were notably higher in patients with migraine, supporting that migraine is often accompanied by psychiatric disorders, of which anxiety and depression are the most widely known and extensively studied. 17,[54][55][56] Indeed, given the longer headache days, higher NRS scores, and headache severity during daily activities as well as higher rate of ER admissions in patients with migraine versus in patients with TTH, our findings are also consistent with previous studies, which reported a relationship of BAI and BDI scores with frequency of episodes and NRS scores in patients with cisgender migraine. 17,57,58 In migraine, the role of testosterone has not been well studied.…”
Section: Discussionsupporting
confidence: 91%
“…BAI is a 21-item, self-reported questionnaire to measure the severity of anxiety during the past week. 37 Each item is scored from 0 to 3, and based on the total score (range 0-63), individuals are categorized to have severe anxiety (scores 26-63), moderate anxiety (scores [16][17][18][19][20][21][22][23][24][25], mild anxiety (scores 8-15), and minimal level of anxiety (scores 0-7). 38 A reliable and valid Turkish form is available.…”
Section: Beck Anxiety Inventorymentioning
confidence: 99%
See 2 more Smart Citations
“…Somatosensory amplification was studied in major depressive disorder, hypochondriasis, asthma, fibromyalgia syndrome and migraine patients with chronic pain (4,16). In migraine patients experiencing chronic pain, somatosensory amplification levels were higher compared to the healthy controls (25). Similarly, somatosensory amplification levels were high in FMS patients (4).…”
Section: Discussionmentioning
confidence: 99%